Agency and geopolitics: Brazilian formal independence and the problem of Eurocentrism in international historical sociology. Issue 3 (3rd May 2020) - Salgado, Pedro
Abstract: The main narratives that explain the development of the modern international order fall short of incorporating the historical peculiarities of processes of state-formation in non-European contexts. To overcome that limitation, this paper argues that class agency must be taken as a core element to understand the social and geopolitical struggles that shape each case of transition towards modern sovereignty in its historical particularity. This is informed by the Brazilian historical experience. In that case, statehood can only be understood as an outcome of the disputes of its ruling landowning class against Portuguese colonialism, mediated by the British informal empire throughout the 19th century. In order to bring all these elements together, I follow the tradition of political Marxism to reconceptualize the very notion of "geopolitics" by grounding it in class-based strategies of reproduction and spatialization. The result is an agency-centred and radically historicist theoretical framework that rejects structuralist transhistorical logics of development. It also argues against the latent Eurocentrism present in theories of state-formation that are grounded on the European experience and simply transposed to other contexts by stressing the agency of non-European subjects in the making of their own history.